2019
DOI: 10.1007/s11881-018-00171-5
|View full text |Cite
|
Sign up to set email alerts
|

Elementary teacher’s knowledge of response to intervention implementation: a preliminary factor analysis

Abstract: In the U.S., many states have adopted Response to Intervention or Multi-tiered Systems of Supports to provide early intervention. However, there is considerable variability in how states and schools implement RTI. Teachers are responsible for using student data from RTI to inform instructional decisions for students with or at risk for dyslexia, so it is necessary to understand the knowledge they have about the structure of RTI in their individual schools. This study reviews the results of an exploratory facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
1
14
0
2
Order By: Relevance
“…Bineham and colleagues (2014) surveyed 619 general and special education administrators nationally and found a notable discrepancy between knowing about RTI and knowing how to implement the tiered framework. Al Otaiba and colleagues (2019) surveyed 139 general and special education teachers to understand their knowledge of Tier 1 and preparedness to make data-based decisions. They found teachers reported greater levels of understanding than preparedness to implement.…”
Section: Research-to-practice Gapmentioning
confidence: 99%
“…Bineham and colleagues (2014) surveyed 619 general and special education administrators nationally and found a notable discrepancy between knowing about RTI and knowing how to implement the tiered framework. Al Otaiba and colleagues (2019) surveyed 139 general and special education teachers to understand their knowledge of Tier 1 and preparedness to make data-based decisions. They found teachers reported greater levels of understanding than preparedness to implement.…”
Section: Research-to-practice Gapmentioning
confidence: 99%
“…Despite the legal mandates and supporting research behind DBDM, many teachers feel that they have inadequate knowledge to accurately read and interpret data (Al Otaiba et al, 2019; Schildkamp et al, 2014). Teachers, administrators, and other educational stakeholders report a general lack of knowledge about DBDM broadly, as well as important subskills within the DBDM framework (e.g., types of data, which tests to use, and how to link data to instruction; Coburn & Turner, 2011).…”
Section: Teacher Knowledgementioning
confidence: 99%
“…Albeit small, Castillo et al (2016b) found a negative and statistically significant relation between experience and knowledge. Because of the contradictory evidence, with some supporting for a positive relation between experience and knowledge, some supporting for no relation, and even one study demonstrating a negative relation, there is a need to further examine the link between teacher experience and knowledge (Al Otaiba et al, 2019; Ruble et al, 2018).…”
Section: Teacher Experiencementioning
confidence: 99%
See 2 more Smart Citations